Implementation Liquidity and Bankrupt Effect Inflation - Hernawan, Moch Arif; Sjarifudin, Didin; Soepriyadi, Irzan; Sujarminto, Yos; Adistie, Gisti Riza (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose in this paper is to see whether the implementation of liquidity, and Inflation with the impact of bankrupt banks in various literatures in the paper with the findings of the corresponding results. Research with qualitative methods by examining literature from papers related to the implementation of liquidity and the effects of bankrupt banks with inflation. Literature comes from existing journals from google scholar, and others. The gap in this paper as a form of contribution to research with the existence of overarching policies, as well as information for the community or customers, is expected to be used in the future by other research to develop as a result of research. In future papers by other researchers, it is hoped that there will be gaps or other variables that can be used by other researchers for other research results in the future